Monitoring health and wellbeing in adolescent track and field (athletics) athletes: A co-creation study - Natalie A. Bunce; Jo Day; Robert H. Mann; Anna Jennings; Alan R. Barker (PLoS ONE, 2026)
Talent Development Environments, such as England Athletics’ Youth Talent Programme (YTP), aim to provide holistic support that promotes long-term athletic and personal development. There is a need for National Governing Bodies to understand athlete health and wellbeing (HWB) to increase athlete availability, wellbeing, and performance. Regarding the YTP, this study aimed to: (1) understand HWB concepts and current monitoring practices; (2) explore design preferences for athlete HWB monitoring; and (3) identify factors that influence the use and implementation of a HWB monitoring system. An online survey was completed by 53 YTP athletes (31 female) capturing demographics, HWB understanding, current monitoring behaviours, and design preferences. Six focus groups and one interview were subsequently conducted with YTP staff (n = 11) and athletes (n = 8). Staff discussions explored current data collection methods, factors that influence system adoption, and integration possibilities. Athlete discussions explored HWB attitudes, factors that influence system adoption, and design preferences. Survey findings indicated that athletes regard monitoring HWB as ‘important’ (36%) or ‘very important’ (26%). However, 62% of athletes do not keep a training diary and 45% do not monitor their HWB, confirming they lack tools and/or knowledge to monitor effectively. Sixty-six percent of athletes who do not monitor would like to improve HWB knowledge. Among those who monitor (55%), the most frequently recorded were training (n = 19) and sleep (n = 14) data. Reflexive thematic analysis generated four interrelated themes: (1) education as a pathway to athlete autonomy and wellbeing ; (2) holistic HWB perspectives ; (3) monitoring practices ; and (4) factors that influence adoption. Findings highlight the importance of HWB education and whole person development. Despite limited formal monitoring knowledge, athletes engage in self-monitoring and are willing to improve HWB knowledge. Preference for mobile accessibility, adaptability, and reminders, together with socio-environmental factors, will inform the design of an athlete HWB monitoring system for the YTP.